Серум сCD40L и галектин-3 у прогнозији пацијената са акутним исхемијским можданим ударом: Серум сCD40L и галектин-3 код акутног исхемијског можданог удара - Chen, Zhiqin; Xiao, Quanhua; Luo, Kunqing; Lin, Shuping; Fan, Zhaoyang; Lai, Xianliang (Journal of Medical Biochemistry, 2025)
[Objective] To explore the value of serum soluble CD40 ligand (sCD40L) and galectin-3 (galectin-3) for predicting the therapeutic effect and prognosis of patients with acute ischemic stroke (AIS).[Methods] 180 AIS patients who were admitted to the hospital between March 2023 and March 2025 were chosen to serve as research participants. All patients received emergency treatment with tenalplase (TNK-tPA) combined with Xuesaitong. Based on the therapeutic impact, patients were split into two groups: an effective group and an ineffective group. The levels of serum sCD40L and galectin-3 in the two groups before treatment and 4 weeks after treatment were detected and compared. Following discharge, all patients were monitored for three months, and based on their modified RANKIN scale (mRS) score, those with a good prognosis and those with a bad outlook were divided into two groups. Utilizing multivariate logistic regression analysis, the risk factors impacting poor prognosis and inadequate treatment in AIS patients were examined. Serum levels of sCD40L and Galectin-3 were analyzed using a receiver operating characteristic (ROC) curve to determine their prognostic value for poor prognosis and ineffective treatment in AIS patients.[Results] Among the 180 research subjects, 146 were effectively treated (effective group), and 34 were ineffective (ineffective group). There were 142 patients with a good prognosis and 38 patients with a poor prognosis, with an incidence of poor prognosis of 21.11%. After four weeks of treatment, serum levels of sCD40L and Galectin-3 were lower in the successful group than in the unsuccessful group (P
Keywords: Серумски растворљиви сКД40 лиганд; Серум галектин-3; Акутни исхемијски мождани удар; Терапеутски ефекат; Прогноза и исход; Предиктивна вредност